Perbandingan tingkat kebocoran mikro resin komposit bulk-filldengan teknik penumpatan oblique incremental dan bulk - Dimas Puja Permana; Billy Sujatmiko; Rinda Yulianti (Faculty of Dentistry, Universitas Gadjah Mada, 2016)
Micoleakage comparison of bulk-fillcomposite beetwen oblique incremental and bulk placement techniques. Resin composite bulk-fill was a new type of resin composite that speed up application process of composite. The concept of bulk-fill composite allows composite to fill at a depth of 4 mm and minimizes polymerization shrinkage. This study aims to determine the comparison of placement techniques (oblique incremental/bulk) of bulk-fill composite on microleakage in class I preparations. Thirty two human maxillary premolar were stored in distilled water, then Class I preparations were made with the depth of the cavity which was 4 mm (3 x 3 x 4). The teeth were randomly divided into two groups, group 1 uses oblique incremental placement technique and group 2 with bulk placement technique. Samples were stored in an incubator at a temperature of 37 °C for 24 hours, then it was thermocycled manually, 100 cycles at temperature between 5 °C and 55 °C. Microleakage was measured using a digital microscope with a 100 X magnification in millimeters using a microscope micrometer calibration ruler with 0,1 mm level of accuracy after immersion in 0,3% methylene blue and sectioned using separating disc. The result of this study revealed that in group 1 microleakage range was 1.0 mm - 2.7 mm with an average 1.625 mm, and in group 2 microleakage range was 3.6 mm - 4.0 mm with an average of 3.763 mm. The data were analyzed using T-test. The analysis showed a significant difference between two groups (p <0.05). The conclusion of this study was bulk-fill composite in class I cavities with oblique incremental placement technique produces less microleakage than bulk placement technique. ABSTRAKResin komposit bulk-fill adalah resin komposit yang dirancang untuk mempercepat proses aplikasi resin komposit. Konsep bulk-fill memungkinkan resin komposit ditumpat sekaligus 4 mm dan mengalami pengerutan polimerisasi minimal. Penelitian ini bertujuan mengetahui efek teknik penumpatan (oblique incremental/bulk) pada tingkat kebocoran mikro resin komposit bulk-fill. Sampel berjumlah 32 gigi premolar rahang atas disimpan di dalam aquades, dipreparasi kavitas kelas I berbentuk persegi, kedalaman kavitas 4 mm (3 x 3 x 4). Sampel dibagi dalam dua kelompok, kelompok 1 restorasi teknik oblique incremental dan kelompok 2 teknik bulk. Sampel kemudian disimpan di dalam inkubator pada suhu 37 °C selama 24 jam, kemudian dilakukan prosedur thermocycling manual 100 putaran pada suhu 5 °C dan 55 °C. Kebocoran mikro diukur menggunakan digital microscope pembesaran 100 x dalam satuan milimeter menggunakan penggaris mikrometer mikroskop dengan ketelitian 0,1 mm setelah sampel direndam dalam larutan methylene blue 0,3% selama 24 jam dan dipotong pada pertengahan restorasi menggunakan separating disc. Hasil pengukuran tingkat kebocoran mikro menunjukkan pada kelompok 1 nilai kebocoran mikro yang terjadi berkisar 1,0 mm – 2,7 mm dengan rata-rata 1,625 mm, pada kelompok 2 kebocoran mikro yang terjadi berkisar 3,6 mm – 4,0 mm dengan rata-rata 3,763 mm. Data di analisis menggunakan uji T-test. Hasil analisis menunjukkan terdapat perbedaan yang signifikan antara kedua kelompok (p < 0,05). Kesimpulan penelitian ini adalah restorasi resin komposit bulk-fill pada kavitas kelas I dengan teknik oblique incremental menghasilkan tingkat kebocoran mikro yang lebih kecil dibandingkan dengan teknik bulk.